2005
DOI: 10.1007/s10096-005-0050-6
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis infection in Spanish travelers to Latin America

Abstract: The aim of the study presented here was to assess the incidence of histoplasma infection in a cohort of 342 individuals in Spain who had traveled to Latin America for the first time. The histoplasmin skin test was positive in 20% of the travelers, and Central America posed a higher risk for infection than South America (p=0.013). Sleeping outdoors (p=0.031) and the duration of travel (p=0.016) were also identified as significant risk factors. Serological testing demonstrated poor overall sensitivity for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…Disease due to H. capsulatum is highly endemic in the Midwestern United States, but low-level endemic disease has also been reported in Mexico, Central America, and South America as well as in parts of Southeast Asia (62,121,207,331,383). Infection occurs when H. capsulatum conidia are inhaled, so activities such as mining, speleology, construction, and agriculture are associated with an increased risk of disease (178).…”
Section: Histoplasmosis the Dimorphic Fungusmentioning
confidence: 99%
“…Disease due to H. capsulatum is highly endemic in the Midwestern United States, but low-level endemic disease has also been reported in Mexico, Central America, and South America as well as in parts of Southeast Asia (62,121,207,331,383). Infection occurs when H. capsulatum conidia are inhaled, so activities such as mining, speleology, construction, and agriculture are associated with an increased risk of disease (178).…”
Section: Histoplasmosis the Dimorphic Fungusmentioning
confidence: 99%
“…Prevalence of imported histoplasmosis is increasing. A recent Spanish study reported a prevalence of 4%, 13 of 342 individuals developed symptomatic histoplasmosis after their first trip to Latin America [16]. In contrast, histoplasmosis has rarely been detected in Austria and has been reported in one human case in 1996 and in a badger in 2000 [6,17].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the fungi may be disturbed for travellers or expatriates by spelunking or mining, various professional activities involving demolishing old buildings, farm work, or sleeping outdoors. 4,5 Primary infection with H capsulatum is usually subclinical, mild, or self-limited among patients who are immunocompetent. After inhalation, the fungi are phagocytized by pulmonary macrophages.…”
Section: Discussionmentioning
confidence: 99%